The Nueva Granada pharmacy of the Company of Jesus: a laboratory for the exploration of medical practices in the province of Santafé in the irst half of the XVIIIth century. (2013)
This paper is focused on the study of an inventory carried out in the pharmacy belonging to Colegio Máximo de Santafé of the Company of Jesus in 1767. This inventory is intended to recognize medical practices performed by missionaries in the province of Santafé during the irst half of the XVIIIth century. In the same way, importance is given to the exchange of healing knowledge between Jesuits and American natives, which was crucial for the colonial and local establishment of the paradigm of Humanist Galenism.